The theoretical framework for impact assessment of the labor code on enterprises - Diep, Dao Mong; Khanh, Nguyen Dao Mai; Dong, Dao The; Nhung, Nguyen Van (Linguistics and Culture Review, 2022)
Labor law plays an important role in regulating the relationship between employees and employers. The Labor Code has made more effective adjustments to enterprises to ensure the interests of employers. However, some regulations still do not meet the requirements set out at the current stage. The article researches the theoretical framework to assess the impact of the Labor Code on enterprises to reflect between the legal theory and the actual law implementation. On that basis, the article will propose solutions to improve the provisions of the Labor Code for enterprises to establish a solid legal corridor to ensure the development of enterprises in the current period.